ANALISIS MAKNA ANGKA ENAM, TUJUH, DELAPAN, SEMBILAN, SEPULUH DALAM PERIBAHASA MANDARIN - Wardhany, Theresa; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractNumeral proverbs are one of the important components in proverbs, it has the same characteristics as proverbs in general, namely a fixed structure, a simple method of compilation, abundant of meanings, easy and clear ways of disclosure. Because the numbers in numeral proverbs contain profound cultural meanings, so the numeral proverbs are also versatile and diverse, this makes it difficult for Mandarin language students to properly understand the meaning of these proverbs and often cause students mistaken in using them. The author chooses Chinese proverbs containing numbers (six, seven, eight, nine and ten) as research objects. The author collected proverbs containing numbers from